Disentangling Facilitation Along the Life Cycle: Impacts of Plant–Plant Interactions at Vegetative and Reproductive Stages in a Mediterranean Forb - García-Cervigón, Ana I.; Iriondo, José M.; Linares, Juan C.; Olano, José M. (Frontiers in Plant Science, 2016)
Facilitation enables plants to improve their fitness in stressful environments. The overall impact of plant-plant interactions on the population dynamics of protégées is the net result of both positive and negative effects that may act simultaneously along the plant life cycle, and depends on the environmental context. This study evaluates the impact of the nurse plant Juniperus sabina on different stages of the life cycle of the forb Helleborus foetidus. Growth, number of leaves, flowers, carpels and seeds per flower were compared for 240 individuals collected under nurse canopies and in open areas at two sites with contrasting stress levels. Spatial associations with nurse plants and age structures were also checked. A structural equation model was built to test the effect of facilitation on fecundity, accounting for sequential steps from flowering to seed production. The net impact of nurse plants depended on a combination of positive and negative effects on vegetative and reproductive variables. Although nurse plants caused a decrease in flower production at the low-stress site, their net impact there was neutral. In contrast, at the high-stress site the net outcome of plant-plant interactions was positive due to an increase in effective recruitment, plant density, number of viable carpels per flower and fruit set under nurse canopies. The naturally lower rates of secondary growth and flower production at the high-stress site were compensated by the net positive impact of nurse plants here. Our results emphasize the need to evaluate entire processes and not only final outcomes when studying plant-plant interactions.